The Quality Of Steamed Brownies Produced From The Substitution Of Sago Flour - Gusnita, Elmia; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of 0%, 15%, 30%, and 45% substitution of sago flour on the quality of the shape, color, aroma, texture and taste of the steamed brownies produced. This type of research is an experiment using a completely randomized design method. The type of data used is primary data obtained from 5 expert panelists by filling out the organoleptic test format. Analysis of the data used is ANOVA, if there is a significant effect, continue with Duncan's test. The results showed that there was an effect on the quality of volume, texture (soft), and texture (fine pores) and there was no effect on the quality of the shape, color, aroma, texture (moist), and taste of the steamed brownies produced. The results of the best steamed brownies in the X2 treatment were in the sweet category, tasted brown, and dark brown in color. It is suggested to the next researcher to process steamed brownies using a substitution of 30% of the amount of wheat flour used.